Solvent-Mediated Control of the Electrochemical Discharge Products of Non-Aqueous Sodium-Oxygen Electrochemistry - Iain Aldous (Angewandte Chemie International Edition, 2016)
The reduction of dioxygen in the presence of sodium cations can be tuned to give either sodium superoxide or sodium peroxide discharge products at the electrode surface. Control of the mechanistic direction of these processes may enhance the ability to tailor the energy density of sodium–oxygen batteries (NaO2: 1071 Wh kg−1 and Na2O2: 1505 Wh kg−1). Through spectroelectrochemical analysis of a range of non‐aqueous solvents, we describe the dependence of these processes on the electrolyte solvent and subsequent interactions formed between Na+ and O2−. The solvents ability to form and remove [Na+‐O2−]ads based on Gutmann donor number influences the final discharge product and mechanism of the cell. Utilizing surface‐enhanced Raman spectroscopy and electrochemical techniques, we demonstrate an analysis of the response of Na‐O2 cell chemistry with sulfoxide, amide, ether, and nitrile electrolyte solvents.